Nadia Boulanger : thoughts on music - Boulanger, Nadia (Eastman studies in music., 2020)
"The impact of Nadia Boulanger (1887-1979) on twentieth-century music was vast: as composer, keyboard performer, conductor, impresario, and pedagogue. Her extensive musical networks included figures such as Fauré, Stravinsky, and Poulenc, and her advocacy helped establish the compositions of her sister Lili Boulanger. Few today realize, though, that Boulanger wrote numerous essays and reviews at various times in her career. These offer unparalleled insight into her thinking and illuminate aspects of musical culture in Europe and America from the from the rare point of view of an internationally prominent female artist. Nadia Boulanger: Thoughts on Music provides a translation and critical edition of selected writings chosen for their quality and interest. The previously published articles and essays have never been reissued since their original appearance; the remaining materials are presented to the reading public here for the first time. The volume renders all these materials widely available, providing an important new resource for teaching and scholarship on twentieth-century music as well as an engaging collection of musical essays for the general reader."--Provided by publisher